Incidence of brain metastasis in lung adenocarcinoma at initial diagnosis on the basis of stage and genetic alterations. (March 2019) - Yang, Bumhee; Lee, Hyun; Um, Sang-Won; Kim, Kyunga; Zo, Jae Il; Shim, Young Mog; Jung Kwon, O; Lee, Kyung Soo; Ahn, Myung-Ju; Kim, Hojoong
Highlights: Brain metastasis (BM) occurred in approximately 16% of lung adenocarcinoma (ADC) patients. BM were found in 3% of stage I lung ADC. Large tumor size, LN involvement, and distant metastases were associated with BM. EGFR mutations were risk factors for BM among never-smokers, K-RAS mutations were risk factors among males. Abstract: Objective: Patients with lung adenocarcinoma (ADC) are at higher risk of the development of brain metastasis (BM), and genetic alterations are associated with BM. Patients and methods: A total of 598 patients with lung ADC in our institution between January 2014 and December 2014 were reviewed retrospectively. We evaluated the incidence of BM by stage and genetic alterations. Results: Of the 598 patients, 97 (16.2%) had BM, which occurred across all stages. The incidence of BM showed a tendency to increase as the stage increased (p < 0.001, trend test). Although patients with EGFR mutations had BM across all stages, those with ALK or K- mutations had BM only in stage III and IV diseases. Regardless of types of mutations, the incidence of BM showed a tendency to increase as the T or N staging increased (p < 0.001 for each of EGFR, ALK, and K-RAS mutations, trend test). Whereas BM incidence showed a tendency to increase as the M staging increased in patients with EGFR-mutant lung ADC (p < 0.001, trend test), there was no linear trend between M staging and ALK (p = 0.469, trend test) or K-RAS mutations (p = 0.066, trend test). After adjusting covariables, EGFR mutations were associated with BM in never-smokers (adjusted OR = 2.07, 95% CI = 1.02–4.34) and K-RAS mutations were risk factors for BM in males (adjusted OR = 3.86, 95% CI = 1.01–14.43). Conclusions: BM occurred in approximately 16% of lung ADC patients, including 3% with stage I diseases. Whereas EGFR-mutant lung ADC had BM across all stages, ALK- or K-RAS-mutant lung ADC had BM only in advanced stages. EGFR mutations were risk factors for BM among never-smokers and K-RAS mutations were risk factors among males.